Implementasi Hak Dan Kewajiban Suami Istri Pada Keluarga Tenaga Kerja Indonesia (TKI) Dalam Perspektif Kitab Dhau’ Al Misbah - Mahmudi, Muhammad; Syafi’i, A. Mustain (State of Islamic Institute Langsa, 2022)
Building sakinah mawaddah warahmah is the main purpose of a marriage. Therefore, the husband and wife must know their rights and obligations. However, for ordinary people, not all can understand it, especially among the Jamberejo Village Community who work as Indonesian Workers. In the book Dhau' al Misbah by KH. M. Hasyim Asy'ari contains the rights and obligations of husband and wife briefly and concisely so that they are easily understood by ordinary people and applied in life. This research uses a qualitative approach with a type of case study research. One of the collection techniques is interviews with several predetermined research subjects who understand the Rights and Obligations of married couples. The results showed that the migrant workers' families in Jamberejo Village had carried out their obligations as husband and wife well. But there are some that cannot be carried out because the husband is abroad.